Novel Ni-MOF / SWCNT composite material, preparation method thereof and application of novel Ni-MOF / SWCNT composite material in lithium battery negative electrode material

By using the in-situ synthesis method in the lithium-ion battery negative electrode material, the problem of poor conductivity of Ni-MOF materials in the prior art is solved, and a lithium-ion battery negative electrode material with high energy density, good cycle stability and safety is achieved.

CN119695123APending Publication Date: 2025-03-25SHANGQIU NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411912270.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to develop lithium-ion battery anode materials that integrate high stability, multi-active sites and high conductivity, and the poor conductivity of the porous Ni-MOF materials, which limit their application.

Method used

A new Ni-MOF/SWCNT composite material was prepared by in-situ synthesis method using SWCNT, nickel nitrate and organic ligand L as raw materials. SWCNT was tightly wrapped around the Ni-MOF surface to form a composite material.

Benefits of technology

The excellent lithium storage performance of lithium-ion battery negative electrode material is achieved, which is characterized by fast charging speed, high capacity and good stability. The 10% Ni-MOF/SWCNT composite material has a charging capacity of 1C with a current density of 1C and a capacity retention rate of 84% after 500 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695123A_ABST
    Figure CN119695123A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a novel Ni-MOF / SWCNT composite material and an application of the novel Ni-MOF / SWCNT composite material in a lithium battery negative electrode material, SWCNT, nickel nitrate and an organic ligand L are adopted, the novel Ni-MOF / SWCNT composite material is prepared through an in-situ synthesis method, the surface of Ni-MOF is tightly wrapped with the SWCNT in the Ni-MOF / SWCNT composite material, the preparation method is simple, the surface of Ni-MOF is tightly wrapped with the SWCNT in the prepared Ni-MOF / SWCNT composite material, and the surface of Ni-MOF is not damaged. The Ni-MOF / SWCNT composite material is used as a lithium ion battery negative electrode material, and shows excellent rapid charging capability, capacity and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic energy storage materials, and specifically relates to a novel Ni-MOF / SWCNT composite material and a preparation method thereof and application thereof in negative electrode materials of lithium batteries.

[0002] The present invention belongs to the catalogue of strategic emerging industries, 1.1 of the new generation of information technology industry, 1.3 of the core electronic industry, and 1.3.4 of the key industry direction of high-end energy storage device materials and device negative electrode materials. Background Art

[0003] The development of new anode materials for lithium-ion batteries (LIBs) is a frontier and hot research topic for achieving clean and sustainable energy storage and conversion. The structure and composition of LIBs anode materials are one of the factors that determine battery performance. However, it is still a challenge to obtain anode materials with advantages such as high stability, multiple active sites and high conductivity. In recent years, metal-organic frameworks (MOFs) materials with porous structures have been widely studied. Among them, Ni-MOF materials with porous structures are conducive to the insertion and deintercalation of lithium ions, which improves the charge and discharge performance of batteries. However, the poor conductivity of porous Ni-MOF materials restricts their application in lithium-ion batteries. On the other hand, single-walled carbon nanotubes (SWCNTs) have high conductivity, high strength, high flexibility, high aspect ratio, and the ability to form a developed network inside the material when added at a low dose, which makes them have broad application prospects in lithium-ion batteries, thermoelectric materials and other fields. Therefore, in terms of lithium battery anode materials, the application of Ni-MOF / SWCNT composites can significantly improve the energy density, cycle stability and safety of batteries. At the same time, its unique structure and performance also provide new ideas for the research and development of new lithium-ion battery negative electrode materials. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides a novel Ni-MOF / SWCNT composite material and a preparation method thereof and application thereof in lithium battery negative electrode materials.

[0005] The object of the present invention is achieved in the following manner: A method for preparing a novel Ni-MOF / SWCNT composite material comprises the following steps: (1) Preparation of Ni-MOF Nickel nitrate hexahydrate and ligand 5-(3-pyridyl)isophthalic acid are added to a mixed solution of N,N-dimethylformamide and tetrafluoroboric acid in a mass ratio of 2-3:1, and the volume ratio of N,N-diethylformamide and tetrafluoroboric acid is 20-30:1. The mixture is heated at 100-120°C for more than 48 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, and dried to obtain a Ni-MOF material. (2) Preparation of Ni-MOF / SWCNT composites Single-walled carbon nanotubes are added in step (1), wherein the mass ratio of the single-walled carbon nanotubes, nickel nitrate hexahydrate and the ligand is (0.5-1.5):(20-30):10, and the mixture is heated at 100-120°C for more than 48 hours. After the reaction is completed, the mixture is cooled to room temperature, washed, filtered and dried to obtain a Ni-MOF / SWCNT composite material.

[0006] The drying temperature in step (1) and step (2) is 50-70°C.

[0007] The Ni-MOF material obtained in step (1) has abundant triangular channels and circular channels in its crystal structure. Each circular channel is surrounded by six triangular channels, and the triangular channels and circular channels form a three-dimensional porous structure.

[0008] The side length of the triangular pore is 12 Å, and the diameter of the circular pore is 10 Å.

[0009] The molecular formula of the new Ni-MOF / SWCNT composite material is [Ni3(μ3-OH)(L)(HCOO)3(H2O)] / SWCNT, where L is 5-(3-pyridyl)isophthalic acid and SWCNT is tightly wrapped on the surface of Ni-MOF.

[0010] The new Ni-MOF / SWCNT composite material is used as anode material for lithium-ion batteries.

[0011] Compared with the prior art, the present invention uses SWCNT, nickel nitrate and organic ligand L as raw materials, and uses an in-situ synthesis method to prepare a new Ni-MOF / SWCNT composite material. In the Ni-MOF / SWCNT composite material, SWCNT is tightly wrapped on the surface of Ni-MOF. The preparation method is simple. The prepared Ni-MOF / SWCNT composite material has excellent lithium storage performance as a negative electrode material for lithium-ion batteries, which is characterized by fast charging speed, high capacity and good stability. As a negative electrode material for lithium-ion batteries, at 25°C, the charging capacity of 10% Ni-MOF / SWCNT at a current density of 1C reaches 438 mAh / g, and the capacity retention rate after 500 cycles is 84%. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a three-dimensional structure diagram of the Ni-MOF material prepared in Example 1 of the present invention.

[0013] Figure 2 3 is the PXRD diagram of Ni-MOF prepared in Example 1 of the present invention and Ni-MOF / SWCNT with different contents.

[0014] Figure 3 It is the SEM picture of Ni-MOF prepared in Example 1 of the present invention and Ni-MOF / SWCNT with different contents.

[0015] Figure 4 It is a charge and discharge curve test diagram of Ni-MOF prepared in Example 1 of the present invention and Ni-MOF / SWCNT with different contents.

[0016] Figure 5 It is a rate performance diagram of Ni-MOF and 10% Ni-MOF / SWCNT prepared in Example 1 of the present invention.

[0017] Figure 6 It is a cycle performance diagram of Ni-MOF and 10% Ni-MOF / SWCNT prepared in Example 1 of the present invention.

[0018] Figure 7 This is a long cycle performance diagram of 10% Ni-MOF / SWCNT in Example 1 of the present invention. DETAILED DESCRIPTION

[0019] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the present invention.

[0020] Example 1 A novel Ni-MOF / SWCNT composite material, the preparation method comprises the following steps: (1) Preparation of Ni-MOF: 20 mg of nickel nitrate hexahydrate and 10 mg of organic ligand L were added to a mixed solution system consisting of 3 mL of N,N-dimethylformamide and 0.1 mL of tetrafluoroboric acid. The thermal reaction was heated at a constant temperature of 120 °C in a constant temperature drying oven for 2 days. After cooling naturally to room temperature, a large amount of colorless block crystals were obtained. The Ni-MOF material was prepared by filtering and drying at 60 °C. The structural formula of organic ligand L is .

[0021] (2) Preparation of Ni-MOF / SWCNT composite materials: 0 mg, 0.5 mg, 1 mg and 1.5 mg of SWCNT were added to the reaction solution of step (1), respectively, and ultrasonically dispersed. The thermal reaction was carried out in a constant temperature drying oven at 120 °C for 48 h, and then naturally cooled to room temperature. The composite materials were washed, filtered and dried at 60 °C to prepare Ni-MOF / SWCNT composite materials with different proportions, which were marked as 0% Ni-MOF / SWCNT, 5% Ni-MOF / SWCNT, 10% Ni-MOF / SWCNT and 15% Ni-MOF / SWCNT, respectively.

[0022] The yield of the Ni-MOF material obtained after drying in Example 1 was 10 mg, and the ligand-based yield was 41.7%. At 150 K, the crystal data of the Ni-MOF material prepared in Example 1 was collected using a Bruker D8 Venture single crystal diffractometer. The data was collected using a Cu-Kα (λ = 1.54178 Å) target ray monochromatized by a graphite monochromator. The specific results are shown in Table 1.

[0023] Table 1 Figure 1 The three-dimensional structure diagram of the Ni-MOF material obtained in step (1) of Example 1. It can be seen from the figure that there are triangular channels and circular channels along the c-axis direction. The side length of the triangular channel is 12 Å, and the diameter of the circular channel is 10 Å. Each circular channel is surrounded by six triangular channels. The triangular channels and circular channels constitute a three-dimensional porous structure Ni-MOF material.

[0024] The structures of the Ni-MOF prepared in Example 1 and the Ni-MOF / SWCNT composite materials with different contents were tested, and the specific results are as follows: Figure 2 Figure 3 is the PXRD pattern of Ni-MOF and Ni-MOF / SWCNT composites with different contents. The diffraction peaks of the PXRD spectra of Ni-MOF and Ni-MOF / SWCNT with different contents are highly consistent with the simulated PXRD spectra, and no impurity peaks appear, which proves that the purity of the Ni-MOF material is very high and the structure of the original Ni-MOF is still maintained after being composited with SWCNT.

[0025] Figure 3 SEM images of Ni-MOF and different content Ni-MOF / SWCNT composites, including Ni-MOF (a), 5% Ni-MOF / SWCNT (b), 10% Ni-MOF / SWCNT (c), 15% Ni-MOF / SWCNT (d). Figure 3It can be seen that with the increase of SWCNT content, the morphology of Ni-MOF does not change much, and SWCNT is tightly wrapped on the surface of Ni-MOF. The results show that the SWCNT dispersion of 10% Ni-MOF / SWCNT composite material is relatively uniform.

[0026] The novel Ni-MOF / SWCNT composite material has excellent electrochemical performance as a negative electrode material for lithium-ion batteries. The electrochemical performance of the Ni-MOF prepared in Example 1 and the Ni-MOF / SWCNT composite materials with different contents were tested.

[0027] First, prepare the negative electrode of lithium-ion battery. The specific preparation method is as follows: the obtained composite is mixed with conductive carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 7:2:1, and N-methylpyrrolidone is used as solvent to evenly coat it on copper foil. After drying in a vacuum drying oven at 60 °C, it is cut into 16 mm diameter discs, and a metal lithium sheet is used as the counter electrode, i.e., the reference electrode. Celgard2500 polypropylene film is used as the diaphragm, and 1 mol L-1 LiPF6-EC (ethylene carbonate) + DMC (dimethyl carbonate) + EMC (ethyl methyl carbonate) (V / V / V=1:1:1) is used as the electrolyte. The positive electrode shell, electrode sheet, diaphragm, lithium sheet and negative electrode shell are placed from bottom to top, and an appropriate amount of electrolyte is added before the diaphragm is placed to assemble a 2032-type button battery. After the assembly is completed, the battery sealing machine is used to quickly pressurize and seal, and after standing for 4 hours, the electrochemical performance is tested after the electrolyte is fully infiltrated. The battery charging and discharging performance was tested using the LandBT2013A charging and discharging instrument produced by Wuhan Landian.

[0028] Figure 4 The charge and discharge curve test diagram of Ni-MOF and Ni-MOF / SWCNT composites with different contents. The results show that when the current density is 0.1C, the 10% Ni-MOF / SWCNT composite material shows good charge and discharge performance.

[0029] Figure 5 Figure 2 is the rate performance diagram of Ni-MOF (a) and 10% Ni-MOF / SWCNT composite (b). The results show that the rate performance of SWCNT in 10% Ni-MOF / SWCNT composite is much higher than that of Ni-MOF.

[0030] Figure 6 The graphs are the cycle performance of the Ni-MOF (a) and the 10% Ni-MOF / SWCNT composite material (b). The results show that at a current density of 0.1C, the cycle performance and capacity retention rate of the SWCNT in the 10% Ni-MOF / SWCNT composite material are much higher than those of Ni-MOF.

[0031] Figure 7 The long cycle performance diagram of 10% Ni-MOF / SWCNT composite material. The results show that at 25 ℃, the charging capacity at a current density of 1C reaches 438 mAh / g, and the capacity retention rate after 500 cycles is 84%.

[0032] Example 2 A novel Ni-MOF / SWCNT composite material, the preparation method comprises the following steps: (1) Preparation of Ni-MOF: 30 mg of nickel nitrate hexahydrate and 10 mg of organic ligand L were added to a mixed solution system consisting of 4 mL of N,N-dimethylformamide and 0.2 mL of tetrafluoroboric acid. The thermal reaction was heated at a constant temperature of 100 °C in a constant temperature drying oven for 60 h. The reaction was naturally cooled to room temperature to obtain a large amount of colorless block crystals. The crystals were filtered and dried at 50 °C to obtain the prepared Ni-MOF material.

[0033] (2) Preparation of Ni-MOF / SWCNT composite material: 1 mg of SWCNT was added to the reaction solution of step (1), ultrasonically dispersed, and thermally reacted in a constant temperature drying oven at 100 °C for 60 h, naturally cooled to room temperature, filtered, and dried at 50 °C to prepare a Ni-MOF / SWCNT composite material.

[0034] Example 3 A novel Ni-MOF / SWCNT composite material, the preparation method comprises the following steps: (1) Preparation of Ni-MOF: 30 mg of nickel nitrate hexahydrate and 12 mg of organic ligand L were added to a mixed solution system consisting of 3 mL of N,N-dimethylformamide and 0.12 mL of tetrafluoroboric acid. The thermal reaction was heated at a constant temperature of 110 °C in a constant temperature drying oven for 72 h. The reaction was naturally cooled to room temperature to obtain a large amount of colorless block crystals. The crystals were filtered and dried at 70 °C to obtain the prepared Ni-MOF material.

[0035] (2) Preparation of Ni-MOF / SWCNT composite material: 1.5 mg of SWCNT was added to the reaction solution of step (1), ultrasonically dispersed, and thermally reacted in a constant temperature drying oven at 110 °C for 72 h, naturally cooled to room temperature, filtered, and dried at 70 °C to prepare a Ni-MOF / SWCNT composite material.

[0036] The present invention adopts SWCNT, nickel nitrate and organic ligand L, and uses an in-situ synthesis method to prepare a novel Ni-MOF / SWCNT composite material. The preparation method is simple. In the prepared Ni-MOF / SWCNT composite material, SWCNT is tightly wrapped on the surface of Ni-MOF. The Ni-MOF / SWCNT composite material is used as a negative electrode material for lithium ion batteries and exhibits excellent fast charging capability, capacity and cycle performance.

[0037] The above is only a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, several changes and improvements can be made without departing from the overall concept of the present invention, which should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a novel Ni-MOF / SWCNT composite material, characterized in that: The following steps are included: (1) Preparation of Ni-MOF Nickel nitrate hexahydrate and ligand 5-(3-pyridyl)isophthalic acid are added to a mixed solution of N,N-dimethylformamide and tetrafluoroboric acid in a mass ratio of 2-3:1, and the volume ratio of N,N-diethylformamide and tetrafluoroboric acid is 20-30:

1. The mixture is heated at 100-120°C for more than 48 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, and dried to obtain a Ni-MOF material. (2) Preparation of Ni-MOF / SWCNT composites Single-walled carbon nanotubes are added in step (1), wherein the mass ratio of the single-walled carbon nanotubes, nickel nitrate hexahydrate and the ligand is (0.5-1.5):(20-30):10, and the mixture is heated at 100-120°C for more than 48 hours. After the reaction is completed, the mixture is cooled to room temperature, washed, filtered and dried to obtain a Ni-MOF / SWCNT composite material.

2. The method for preparing the novel Ni-MOF / SWCNT composite material according to claim 1, characterized in that: The drying temperature in step (1) and step (2) is 50-70°C.

3. The method for preparing the novel Ni-MOF / SWCNT composite material according to claim 1, characterized in that: The Ni-MOF material obtained in step (1) has abundant triangular channels and circular channels in its crystal structure. Each circular channel is surrounded by six triangular channels, and the triangular channels and circular channels form a three-dimensional porous structure.

4. The method for preparing the novel Ni-MOF / SWCNT composite material according to claim 3, characterized in that: The side length of the triangular pore is 12 Å, and the diameter of the circular pore is 10 Å.

5. A novel Ni-MOF / SWCNT composite material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The molecular formula of the Ni-MOF / SWCNT material is [Ni3( μ 3-OH)(L)(HCOO)3(H2O)] / SWCNT, L is 5-(3-pyridyl)isophthalic acid, and SWCNT is tightly wrapped on the Ni-MOF surface.

6. The novel Ni-MOF / SWCNT composite material according to claim 5 is used as a negative electrode material for lithium-ion batteries.